Randomized Trial of Hepatic Artery Embolization for Hepatocellular Carcinoma Using Doxorubicin-Eluting Microspheres Compared With Embolization With Microspheres Alone - Brown, Karen T; Do, Richard K; Gonen, Mithat; Covey, Anne M; Getrajdman, George I; Sofocleous, Constantinos T; Jarnagin, William R; D'Angelica, Michael I; Allen, Peter J; Erinjeri, Joseph P; Brody, Lynn A; O'Neill, Gerald P; et al. (Journal of clinical oncology, 2016)
Transarterial chemoembolization is accepted therapy for hepatocellular carcinoma (HCC). No randomized trial has demonstrated superiority of chemoembolization compared with embolization, and the role of chemotherapy remains unclear. This randomized trial compares the outcome of embolization using microspheres alone with chemoembolization using doxorubicin-eluting microspheres. At a single tertiary referral center, patients with HCC were randomly assigned to embolization with microspheres alone (Bead Block [BB]) or loaded with doxorubicin 150 mg (LC Bead [LCB]). Random assignment was stratified by number of embolizations to complete treatment, and assignments were generated by permuted blocks in the institutional database. The primary end point was response according to RECIST 1.0 (Response Evaluation Criteria in Solid Tumors) using multiphase computed tomography 2 to 3 weeks post-treatment and then at quarterly intervals, with the reviewer blinded to treatment allocation. Secondary objectives included safety and tolerability, time to progression, progression-free survival, and overall survival. This trial is currently closed to accrual. Between December 2007 and April 2012, 101 patients were randomly assigned: 51 to BB and 50 to LCB. Demographics were comparable: median age, 67 years; 77% male; and 22% Barcelona Clinic Liver Cancer stage A and 78% stage B or C. Adverse events occurred with similar frequency in both groups: BB, 19 of 51 patients (38%); LCB, 20 of 50 patients (40%; P = .48), with no difference in RECIST response: BB, 5.9% versus LCB, 6.0% (difference, -0.1%; 95% CI, -9% to 9%). Median PFS was 6.2 versus 2.8 months (hazard ratio, 1.36; 95% CI, 0.91 to 2.05; P = .11), and overall survival, 19.6 versus 20.8 months (hazard ratio, 1.11; 95% CI, 0.71 to 1.76; P = .64) for BB and LCB, respectively. There was no apparent difference between the treatment arms. These results challenge the use of doxorubicin-eluting beads for chemoembolization of HCC.